DAMPAK PEMBANGUNAN PERUMAHAN TERHADAP KONDISI LINGKUNGAN, SOSIAL, DAN EKONOMI MASYARAKAT KELURAHAN BINJAI, KECAMATAN MEDAN DENAI - Lumban Gaol, Jhon Feliks; Pinem, Dessy Eresina; Sembiring, Rahmad Dian (Jurnal Sains dan Teknologi ISTP, 2024)
The increasing number of residents urbanizing to Medan City has an impact on limited land and physical resources in Medan City. The limited land area in Medan City has caused Medan City to experience development into suburban areas, this is what is happening in Binjai Village, Medan Denai District. This triggers an impact on social, economic and environmental conditions with housing development. This situation is interesting to study, with the research question: what are the social, economic and environmental impacts of housing development in Binjai Village? It is important to know the impacts before and after housing development. This research aims to examine the impacts that arise after housing construction on social, economic and environmental conditions in Binjai Village. The method used is descriptive quantitative. The data collection technique was carried out using questionnaires assisted by interviews and field observations. The final results of the impact research following housing construction consist of 3 impacts, namely social, economic and environmental. The social impact is in the form of changes in people's lifestyles which are more consumerist, decreasing crime rates. The impact on the economy is in the form of increasing people's income, increasing land prices. The impact on the environment is in the form of changes in land use, improvements to the drainage network and road network.